Zbornik Radova Trideset Devetog Simpozijuma O Novim Tehnologijama U Poštanskom I Telekomunikacionom Saobraćaju – Postel 2021 2021
DOI: 10.37528/ftte/9788673954455/postel.2021.003
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Location Analysis of Micro Distribution Centers for Last Mile Delivery

Abstract: Last mile delivery represents an intensely competitive business and the position of postal companies, as a traditional provider of this service, is under the increasing pressure. The aim of this paper is to provide a review of the current process of parcel deliveries of Public Enterprise Post of Serbia and to assess the possibility for introduction of alternative models. More precisely, for Belgrade urban area, we analyze the potential for transition from the current hub-and-spoke model to a multy hub distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Rusul et al highlight that micro-mobility is increasingly recognized as an urban mode of transport due to its potential to reduce the use of private vehicles for personal needs or large-scale vehicle use for mail or package delivery, with increasing preference for micro-mobility for short-distance travel [8]. A study has shown the positive results of micro-mobility implementation by the Serbian Public Enterprises Post Office to review the process of package or mail deliveries and to evaluate the possibility of applying alternative models [9]. Micro-mobility vehicles began to take place among the essential means of transportation in terms of human mobility because human mobility has been an important factor in the human necessities of life.…”
Section: Introductionmentioning
confidence: 99%
“…Rusul et al highlight that micro-mobility is increasingly recognized as an urban mode of transport due to its potential to reduce the use of private vehicles for personal needs or large-scale vehicle use for mail or package delivery, with increasing preference for micro-mobility for short-distance travel [8]. A study has shown the positive results of micro-mobility implementation by the Serbian Public Enterprises Post Office to review the process of package or mail deliveries and to evaluate the possibility of applying alternative models [9]. Micro-mobility vehicles began to take place among the essential means of transportation in terms of human mobility because human mobility has been an important factor in the human necessities of life.…”
Section: Introductionmentioning
confidence: 99%